2019
DOI: 10.1111/pcn.12909
|View full text |Cite
|
Sign up to set email alerts
|

Paternal age contribution to brain white matter aberrations in autism spectrum disorder

Abstract: Aim: Although advanced parental age holds an increased risk for autism spectrum disorder (ASD), its role as a potential risk factor for an atypical white matter development underlying the pathophysiology of ASD has not yet been investigated. The current study was aimed to detect white matter disparities in ASD, and further investigate the relationship of paternal and maternal age at birth with such disparities.Methods: Thirty-nine adult males with high-functioning ASD and 37 typically developing (TD) males wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 83 publications
1
4
0
Order By: Relevance
“…Our study also found significant differences in FA of the bilateral UF between the ASD and control groups; this finding confirmed the abnormalities of the UF in ASD individuals, including decreased FA (Jou et al, 2016;Koshiyama et al, 2020;Samson et al, 2016) and increased MD (Catani et al, 2016;Yassin et al, 2019), reported in a number of previous studies. The UF participates in the second functional network of the limbic system, the temporo-amygdala-orbitofrontal network, and plays an important role in the integration of visceral and emotional states with semantic memory and behavior (Catani et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Our study also found significant differences in FA of the bilateral UF between the ASD and control groups; this finding confirmed the abnormalities of the UF in ASD individuals, including decreased FA (Jou et al, 2016;Koshiyama et al, 2020;Samson et al, 2016) and increased MD (Catani et al, 2016;Yassin et al, 2019), reported in a number of previous studies. The UF participates in the second functional network of the limbic system, the temporo-amygdala-orbitofrontal network, and plays an important role in the integration of visceral and emotional states with semantic memory and behavior (Catani et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…An example is the suggestion-assisted reproduction and in vitro fertilization is involved, but follow-up studies demonstrated no risk of ASD in children born after assisted reproduction [23,24]. One factor that has been correlated with autism is paternal age [4,9,15] and sperm DNA methylation alterations [11,25]. Previous studies have shown a hypermethylation of sperm DNA is associated with male infertility, abnormal sperm parameters and increasing age [13,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are both paternal and maternal transmission of ASD, the prevalence of paternal transmission is higher in most populations. One of the main factors proposed to be involved is paternal age [9], with an increased percentage risk of 28% between 40-49 years and nearly 70% when greater than 50 years of age [4]. Increased paternal age has been associated with epigenetic DNA methylation alterations in sperm [10], including specific genes associated with autism [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…All participants are ethnically Japanese and were recruited at The University of Tokyo Hospital. The diagnostic criteria for schizophrenia, and ASD and inclusion and exclusion criteria can be found elsewhere 29 31 , additionally, a comprehensive explanation was added to the supplemental materials. The ethical review board of The University of Tokyo Hospital approved this study (Nos.…”
Section: Methodsmentioning
confidence: 99%